The Impact of a Comorbid Spinal Cord Injury on Cognitive Outcomes of Male and Female Patients with Traumatic Brain Injury. Issue 7 (21st September 2020) - Mollayeva, Tatyana; Sutton, Mitchel; Escobar, Michael; Hurst, Mackenzie; Colantonio, Angela
Abstract : Introduction: Evidence of the effect of comorbid spinal cord injury (SCI) on cognitive outcomes in persons undergoing rehabilitation following newly diagnosed traumatic brain injury (TBI) is limited. We conducted a population‐based study to investigate this effect. Objective: To compare cognitive outcomes in patients with TBI with and without a comorbid SCI. Setting/Participants: Adult patients diagnosed with TBI were identified and followed for 1 year through provincial health administrative data; those who entered inpatient rehabilitation were studied. Design: A retrospective matched cohort study using the National Rehabilitation Reporting System data of all acute care and freestanding rehabilitation hospitals in Ontario, Canada. Main Measures: The exposure was a comorbid SCI in patients with diagnosed TBI. Exposed patients were matched to unexposed (TBI‐only) on sex, age, injury severity, and income, in a ratio of one to two. Gain differences in the cognitive subscale of the Functional Independence Measure were compared between exposed and unexposed patients using multivariable mixed linear model, controlling for comorbidity propensity score, gains in motor function, and rehabilitation care indicators. Results: Over the first year post injury, 12 750 (0.84%) of all TBI patients entered inpatient rehabilitation, of whom 1359 (10.66%) had a comorbid SCI. A total of 1195 exposed patients (65.4% male, mean age 50.9 ± 20.6 for male and 61.8 ± 21.8 for female patients) were matched to 2390 unexposed patients. Controlling for confounding, exposed patients had lower cognitive gain (beta −0.43; 95% CI −0.72, −0.15), for both male (beta −0.39; 95% CI −0.75, −0.03) and female (beta −0.51; 95% CI −0.97, −0.05) patients. The adverse effects of comorbid SCI were driven largely by lower gains in problem solving and comprehension. Conclusions: Adult patients with TBI and comorbid SCI showed a lower cognitive domain response to inpatient rehabilitation than patients with TBI alone. Identifying patients at risk for worse cognitive outcomes may facilitate the development of targeted strategies that improve cognitive outcomes.